HERBAGE YIELD, MORPHOLOGICAL DEVELOPMENT AND NUTRITIVE VALUE OF LUCERNE DURING GROWTH SEASON IN CENTRAL SLOVENIA: ANALYSIS OF TIME PATTERNS - Jure ČOP; Katarina KOŠMELJ; Tomaž ŽNIDARŠIČ; Jože VERBIČ (Acta Agriculturae Slovenica, 2018)
Cutting time is a pivotal factor affecting herbage yield and nutritive value of forage crop monocultures. Therefore, our objectives in this lucerne study were to analyse temporal patterns of herbage yield, morphological development and quality parameters over growth season, and to relate these patterns to the time of cutting. A field experiment in split-plot design with two block replications was conducted in Ljubljana in 2016. Four growth cycles (C1-C4) were assigned to the main plots, and nine weekly intervals at which herbage yield was measured and herbage samples taken were assigned to the sub-plots. Dry-matter herbage yield accumulated faster during the first half of the season than during the second one. It peaked early in each of the last two growth cycles and after that started to decrease. Statistical analysis showed that linear regression models are acceptable to describe time patterns of morphological development stages (MSW) and contents of crude protein (CP), neutral detergent fibre (NDF) and net energy for lactation (NEL). MSW increased faster during the summer than during the spring or autumn, but only C1 was distinct in this pattern. Lucerne forage quality was generally the highest in C1 mainly due to slower morphological development. This high quality reflected more in NDF and NEL than in CP. In respect of the quality, only C4 at the beginning of the growth was equivalent to C1. Considering yield and content of NEL optimal age of lucerne at cutting was from 28 to 35 days in spring and summer and from 35 to 42 days in autumn.